Exploring the Roles of the L2 Motivational Self System in the English Learning Achievement of Thai High School Learners - Pattiya, Jitra; Chaiyasuk, Dr.Intisarn (KKU Research Journal (Graduate Studies) Humanities and Social Sciences, 2023)
This research investigated the roles of the Second Language (L2) Motivational Self System (L2MSS) in the English learning achievement of Thai high school learners and the success in learning English of Thai high school students. By adapting the frameworks of the L2 MSS, which consisted of the ideal L2 self, ought-to L2 self, and L2 learning experience, this research aimed to explore perceptions to understand the learners’ motivation that can impact English learning achievement. The sample included 120 twelfth-grade students selected through random sampling from four typical English as a Foreign Language (EFL) classes at a local secondary school. Data were collected through a questionnaire and in-depth interviews, following a mixed-method study format. The questionnaire aimed to identify various characteristics of Thai EFL learners. Meanwhile, ten participants were invited for interviews to ascertain the perceptions of Thai high school learners regarding L2 MSS in their English learning achievements. The findings from the questionnaire indicated that the ideal L2 self was the most important factor, followed by the L2 learning experience, while the ought-to L2 self was the least influential. Moreover, the interview results suggested that both high and low achievers appeared to share common goals in learning English. Therefore, this research provides teachers with insights into creating more visionary, motivational approaches in the language classroom, as the ideal L2 self becomes the driving force for performance.